Aberrant DNA hypermethylation reduces the expression of the desmosome‐related molecule periplakin in esophageal squamous cell carcinoma. (12th January 2015) - Otsubo, Takeshi; Hagiwara, Teruki; Tamura‐Nakano, Miwa; Sezaki, Takuhito; Miyake, Oki; Hinohara, Chihaya; Shimizu, Toshio; Yamada, Kazuhiko; Dohi, Taeko; Kawamura, Yuki I.
Abstract: Periplakin (PPL), a member of the plakin family of proteins that localizes to desmosomes and intermediate filaments, is downregulated in human esophageal squamous cell carcinoma (ESCC). Little is known, however, about the molecular mechanism underlying the regulation of PPL expression and the contribution of PPL loss to the malignant property of the cancer is unclear. We demonstrated that PPL mRNA expression was significantly reduced in ESCC tissues compared with that in normal tissues. Therefore, we hypothesized that CpG hypermethylation is the cause of the downregulation of PPL. Bisulfite‐pyrosequencing of 17 cases demonstrated that the frequency of PPL methylation was higher in ESCC tissues than in normal tissues. When human ESCC cell lines were treated with 5‐aza‐2′‐deoxycytidine (5‐aza‐dC), a DNA‐methyltransferase inhibitor, PPL transcription was induced. Human KYSE270 ESCC cells do not stratify under ordinary culture conditions and rarely produce desmosomes; however, the forced expression of PPL promoted cell stratification. PPL induction also promoted adhesion to extracellular matrix but delayed cell migration. The abundance of desmosome‐like structures was greatly increased in PPL transfectant as determined by transmission electron microscopy. Very low expression of another desmosome protein EVPL in ESCC, even in PPL transfectant, also supported the significant role of PPL in desmosome formation and cell stratification. Our results first indicate that the downregulation of PPL mediated by DNA hypermethylation, which may play an important role in the loss of ESCC stratification and likely in metastatic phenotype. Abstract : A desmosomal protein preplakin (PPL) is reduced in esophageal squamous cell carcinoma (ESCC). Here, we first report DNA methylation of PPL in ESCC and that PPL plays significant role in desmosome formation, squamous cell stratifying, adhesion to extracellular matrix and delayed migration.